2016
DOI: 10.1007/s11739-016-1397-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of circulating microparticles in obesity after weight loss

Abstract: A definitive relationship between adiposity and MP production is yet to be demonstrated. The aim of our study was to prospectively evaluate the levels of microparticles (MP) in a group of 20 III degree obese patients before and after weight loss. Plasma levels of annexin V-MP, endothelial-derived MP, platelet-derived MP (CD61+ and P-Selectin+), leukocyte-derived MP, tissue factor-bearing (TF+) and CD36+MP were prospectively measured in 20 patients with III degree obesity (BMI ≥ 40 kg/m(2)) before (T0) and 3 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 35 publications
3
27
1
Order By: Relevance
“…An interesting observation in the present study was that CD36+ MVs did not differ significantly from baseline to the three-month follow-up. This result is in contrast to a study conducted by Campello et al, in which CD36+ MVs decreased significantly from baseline to three and twelve-months follow-up visits [ 39 ]. Interestingly, although CD36+ MVs were unaltered, a significant decrease was seen in sCD36 in the present cohort.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…An interesting observation in the present study was that CD36+ MVs did not differ significantly from baseline to the three-month follow-up. This result is in contrast to a study conducted by Campello et al, in which CD36+ MVs decreased significantly from baseline to three and twelve-months follow-up visits [ 39 ]. Interestingly, although CD36+ MVs were unaltered, a significant decrease was seen in sCD36 in the present cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies that have previously examined the impact of bariatric surgery on EMV concentrations have yielded conflicting results. In line with the present study, both Campello et al [ 39 ] and Cheng et al [ 40 ] reported that levels of various phenotypes of MVs including platelet MVs, EMVs and MMVs decreased significantly in obese subjects after bariatric surgery. Conversely, Stepanian et al [ 34 ] reported no differences in platelet MVs and EMVs one year after subjects had undergone bariatric surgery, which was later supported by a study conducted by Witczak et al [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Identification of more precise changes pertaining to adipobiology that take place following between clinical studies evaluating changes in circulating EVs are limited by the fact that establishing a gold standard method for EV isolation to be adopted across laboratories has only recently been a focus of the International Society of Extracellular Vesicles (ISEV) [26], although our adopted approach is one of the most commonly accepted protocols that we have introduced to yield consistent samples and results. This approach was not used in the studies by other authors [22][23][24] and similarly the EV analysis in the studies we cited was performed by flow cytometry which is typically not sensitive enough to detect EVs of exosomal origin and differs from our immunophenotyping method which we adapted for EV analysis specifically [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The same study also showed that obese patients had a significantly higher median peak thrombin and increased median endogenous thrombin potential compared to controls [11]. The same group of researchers has shown that after sleeve gastrectomy, the decrease of BMI in morbidly obese subjects was matched with a decrease of circulating microparticles of endothelial, platelet, and leukocyte origin [12]. …”
Section: Introductionmentioning
confidence: 99%